Association of sleep quality with lower urinary tract symptoms/benign prostatic hyperplasia among men in China: A cross-sectional study - Li, Yifan; Zhou, Xianghong; Qiu, Shi; Cai, Boyu; Wang, Sheng; Chen, Lei; Hu, Dan; Jiang, Zhongyuan; Wang, Mingda; Xiong, Xingyu; Jin, Kun; Wei, Qiang; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: As the population aged, voiding dysfunction has been steadily rising among males during the past decade. Increasing evidence showed that sleep disorders are associated with an increasing risk of various diseases, but the association between sleep disorders and lower urinary tract symptoms (LUTS) / benign prostatic hyperplasia (BPH) among Chinese males have not been well characterized. Methods: We conducted a cross-sectional analysis of data from West China Natural Population Cohort Study (WCNPCS) 2019-2021. Sleep quality was assessed by Pittsburgh sleep quality index (PSQI) in Chinese version. LUTS/BPH as a dependent variable of a binary variable, assessed by a self-reported questionnaire. Multivariate logistic regression analysis were performed to evaluate the correlation between sleep disorders and the risk of LUTS/BPH after adjusting for confounding factors. Results: 11,824 eligible Chinese men participated in this cross-sectional survey. In multivariate logistic regression analysis, after adjusting for confounding variables, global PSQI score (OR: 1.257, 1.119-1.411, p<0.001) and its six compounds (Subjective sleep quality: OR: 1.376, 1.004-1.886, p=0.048; Sleep latency: OR: 0.656, 0.557-0.773, p<0.001; Sleep duration: OR:1.441, 1.189-1.745, p<0.001; Habitual sleep efficiency: OR: 1.369, 1.193-1.570, p<0.001; Daytime dysfunction: OR: 1.702, 1.278-2.267, p<0.001) except the use of sleep drug subgroup were significantly positively correlated with LUTS/BPH prevalence. Significant interaction effects were observed in age subgroups (age-young group: age<51; age-middle group: 51≤age≤61; age-older group: age>61) (P < 0.05). Among older participants, sleep disorders were more significantly associated with the risk of LUTS/BPH. Conclusions: There was a significant association between poor sleep quality and increased prevalence of LUTS/BPH, especially among the elderly male population, suggesting an important role of healthy sleep in reducing prostate disease burden.